Perceived dyspnea and experience of hospitalized patients with acute decompensated heart failure undergoing an early MObilization protocol with immersive Virtual rEality: MOVE study protocol for a parallel superiority randomized clinical trial - Iasmin Borges Fraga; Larissa Gussatschenko Caballero; Pedro Dal Lago; João Lucas Campos de Oliveira; Marina Scherer; Mauren Porto Haeffner; Eneida Rejane Rabelo-Silva (Trials, 2023)
Abstract Background Immersive virtual reality (VR) is an innovative strategy for inpatient rehabilitation programs. Using immersive VR in early mobilization protocols has not yet been investigated in the setting of hospitalized patients with acute decompensated heart failure (ADHF), especially to improve perceived dyspnea, a common symptom of heart failure (HF). Methods This is a single-center parallel superiority randomized clinical trial. The study will be conducted at a public teaching hospital in Brazil from January 2023 to January 2024. The sample will include adult patients with ADHF hospitalized for at least 24 h, randomly assigned in a 1:1 ratio to the control (standard early mobilization protocol conducted in the intensive care unit (ICU)) or intervention group (the same standard early mobilization protocol but associated with immersive VR). The primary outcome will be assessing perceived dyspnea, and the secondary outcome will be assessing patient experience. Discussion Using immersive VR in early mobilization protocols in the ICU is expected to improve perceived dyspnea in patients with ADHF as well as patient experience regarding care. This study has the potential to increase patient adherence to early mobilization protocols in the setting of ADHF as well as to promote a positive patient experience. Filling this gap could promote the rational incorporation of technologies in health care. Trial registration This study protocol is in its first version. ClinicalTrials.gov NCT05596292. Registered on 1 December 2022.